Prototype of Wideband Air Sonar Based on STM32 - OKOŃ-FĄFARA, Marta; KAWALEC, Adam Marian; FĄFARA, Bartłomiej Łukasz (Archives of Acoustics, 2017)
The paper presents a project of a low-cost prototype version of a wideband air sonar and the problems occurring during its development process. The aim of this work was to design a short range air sonar capable of creating the reflectivity map of its surroundings using an arbitrary shape wideband signal. The transmitting and receiving transducers that have been chosen for this application typically work in pulsed operation modes. Therefore, dedicated output and input circuits had to be designed to expand its capabilities without information losses. The signal generation, transmission, reception and storage are managed by a Discovery evaluation board with a STM32 microcontroller. The receiving data are saved on a SD card and are processed off-line.